Factors Influencing Farmers’ Climate Change Adaptation in Northern Ghana Evidence from Subsistence Farmers in Sissala West, Ghana - Fagariba, Clifford James; Song, Shaoxian; Soule, Serge K. G. (2018)
Most African countries are vulnerable to climate change as a result of poverty, weather extremes, and insufficient governmental agricultural support. Using the area of Sissala West District, factors influencing farmers’ adaptation to climate change and strategies used to avert climate change impact were determined. A total of 330 small-scale farmers were sampled and their views were determined Using logits regression model, weighted average index, and frequency table. Weighted average index was used to rank opinions of 150 key informants in focus group discussions. Using logits regression model, the study indicated irregular rainfall, high temperature, weather information, and high evaporation as the factors compelling farmers to adapt to climate change. Weighted Average Index used to measure weather extremes revealed that drought and temperature had the highest level of occurrence. Furthermore, climate change adaptation strategies assessed in the study showed that agroforestry practices, drought-resistant crops, and mulching were the most preferred methods. The study concluded that farmers’ ability to adapt to climate change can be improved if Environmental Protection Agency and Ministry of Food and Agriculture intensify climate adaptation campaigns, increase access to weather information, and training farmers on adaptable strategies including, but not limited to, alternative sources of livelihood.
Keywords: Agriculture; Climate and Agriculture